2008
DOI: 10.1214/009053607000000884
|View full text |Cite
|
Sign up to set email alerts
|

On deconvolution with repeated measurements

Abstract: In a large class of statistical inverse problems it is necessary to suppose that the transformation that is inverted is known. Although, in many applications, it is unrealistic to make this assumption, the problem is often insoluble without it. However, if additional data are available, then it is possible to estimate consistently the unknown error density. Data are seldom available directly on the transformation, but repeated, or replicated, measurements increasingly are becoming available. Such data consist … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
171
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 29 publications
0
171
0
Order By: Relevance
“…Since assuming ε symmetric is equivalent to assuming f * ε real-valued, we can see that (A1) is equivalent to the assumption 2.2 in Delaigle et al [2008]. Therefore, Assumption (A1) implies that ∀t ∈ R, f * ε (t) ∈ R * + .…”
Section: Assumption(a1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since assuming ε symmetric is equivalent to assuming f * ε real-valued, we can see that (A1) is equivalent to the assumption 2.2 in Delaigle et al [2008]. Therefore, Assumption (A1) implies that ∀t ∈ R, f * ε (t) ∈ R * + .…”
Section: Assumption(a1)mentioning
confidence: 99%
“…Therefore, given that E e it(ε −j1 −ε −j2 ) = E e it(Y −j1 −Y −j2 ) and under the hypothesis (A1), Delaigle et al [2008] propose the following estimator of (f * ε )…”
Section: Assumption(a1)mentioning
confidence: 99%
“…of  * in a simpler way (see Markatou (1996), Li andVuong (1998), Delaigle, Hall, and Meister (2008)) by noting that…”
Section: Repeated Measurementsmentioning
confidence: 99%
“…In Carroll and Hall (1988) he provided the minimax rate of convergence for nonparametric density estimation. In Delaigle, Hall and Meister (2008), Peter studied the problem in case the density of U is unknown but is estimated from repeated contaminated measurements. Recently, in his last paper on the topic (Delaigle and Hall, 2016), he demonstrated that one may estimate the density of X using its phase function.…”
Section: Introductionmentioning
confidence: 99%